FAILURE ANALYSIS OF FRACTURED AIR COMPRESSOR BEARING BOLT HOLES - LIU DiHui; HE Yao (Jixie qiangdu)
Bolt holes take place fracture on air compressor bearing of a dry mortar truck,it leads to bolt are easy to be pulled out. Because of the special structure of air compressor,air compressor bearing bolt holes are exerted on dynamic load,the dynamic load is difficult to directly get in the test. Uses the dynamics simulation software adams,the coupled model is set up,use spring replace bolts,to simulation analyze the stress of the bolt,Finally get the tensile force of the bolt holes,and determine the cause of the bolt holes occurred fracture. Results show that the maximum tensile stress on the bolt holes are more than tensile strength,resulting in bolt holes occurred fracture.